ANALYSIS OF CHARACTERIZATION OF THE MAIN CHARACTERS OF “FIRST THEY KILLED MY FATHER” MOVIE BY ANGELINA JOLIE - Trisnian Ifianti (UIBU, 2020)
Literary work, especially film, gives life a lot of inspiration. Movie makes the reader aware that the story that happens in a movie is a reflection of a real life. Characters are characters in stories, and traits are the reasons why a character does things. In fact, there are several explanations why in the Movie Script